Use of δ15N and δ18O Values for Nitrate Source Identification under Irrigated Crops: A Cautionary Vadose Zone Tale. Issue 3 (1st May 2017) - Loo, Shawn E.; Ryan, M. Cathryn; Zebarth, Bernie J.; Kuchta, Shawn H.; Neilsen, Denise; Mayer, Bernhard
Abstract : Source nitrogen (N) identification of leachate or groundwater nitrate is complicated by N source mixing and N and oxygen (O) isotope fractionation caused by microbial N transformations. This experiment examined the δ 15 NNO3 and δ 18 ONO3 values in leachate collected over 1 yr at 55 cm below raspberry ( Rubus idaeus L.) plots receiving either synthetic fertilizer (FT) or poultry manure (MT). The large ranges of δ 15 NNO3 (FT: −2.4 to +8.7‰, MT: +1.6 to +9.6‰) and δ 18 ONO3 (FT: −9.9 to −0.3‰, MT: −10.9 to +1.7‰) values in leachate collected under crop rows prohibited the reliable identification of the applied N sources on individual sampling dates. However, the mass‐weighted average δ 15 NNO3 (FT: +3.2‰, MT: +7.3‰) values in leachate were significantly different and can be explained by accounting for the estimated contributions of nitrate and δ 15 NNO3 values of the various N sources, including applied fertilizer (−0.7‰) or manure (+7.9‰), nitrate‐rich irrigation water (+9.0‰), and nitrate from soil N mineralization and nitrification (FT: +3.7‰, MT: +4.6‰; the seasonal timing of which is unknown). This study illustrates the importance of characterizing all major N sources and considering the seasonal variation of these sources and of N cycling processes, as they contribute to the δ 15 NNO3 values of leachate. Core Ideas: Temporal variation in δ 15 NNO3 and δ 18 ONO3 prevented reliable N source distinction. N treatments differed using mass‐weighted annual average δ 15 NNO3 and δ 18 ONO3 values. Annual average δ 15 NNO3 was predictable using estimated N source contributions. Soil N and irrigation water NO3 contributed significantly to the leachate mass flux.